Rancangan Proses Pembelian Menggunakan Sistem ERP SAP S/4HANA Modul Material Management (MM) Menggunakan Metode SAP Activate Studi Kasus: Perusahaan Distribusi FMCG XYZ Malaysia Sdn. Bhd. - Maulana Karnawidjaja Wahyu; Rizal Ramdan Padmakusumah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
XYZ Malaysia Sdn. Bhd. is a company engaged in the distribution and sales of snack food products in Malaysia, currently utilizing the SAP Business One (SAP B1) Enterprise Resource Planning (ERP) system to support its operational activities. As the business grows, the existing system is considered less capable of optimally supporting operational needs, particularly in terms of system security, data accessibility, and information integration with the holding company in Indonesia. Therefore, the implementation of a more advanced ERP system, such as SAP Business Suite S/4HANA, is considered a more suitable solution. This study aims to design an Enterprise Resource Planning (ERP) system using the SAP S/4HANA Material Management (MM) module. The research method used is qualitative with a descriptive approach, and the system design is conducted using the SAP Activate Methodology in the Explore phase, which includes business requirement analysis, evaluation of existing processes (as-is), identification of best practices, and gap analysis. The results show that the proposed system design SAP S4/HANA is capable of supporting current business processes.